PENGARUH GOOD CORPORATE GOVERNANCE DAN RASIO KEUANGAN TERHADAP FINANCIAL DISTRESS - Kusanti, Okta; Andayani, Andayani (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
The purpose of this research is to test the influence of good corporate governance (institutional ownership, managerial ownership, the number of board of director, the number of board of commissioner, the number of audit committee) and the financial ratio (liquidity, leverage, operating capacity, profitability) to the financial distress. The research samples are 14 companies which have been selected by using purposive sampling of the manufacturing companies which are listed in Indonesia stock exchange in 2010-2013 periods. The financial statement has been obtained from the official website i.e.:http://www.idx.co.id/idid/beranda/perusahaan tercatat/laporankeuangantahunan.aspx and from the Indonesia Stock Exchanges in STIESIA. The research method has been done by using quantitative method with the logistic analysis technique and it is also done by using the statistic instruments of SPSS 20.0 version. The result of this research shows that the institutional ownership does not have any influence to the financial distress, the managerial ownership does not have any influence to the financial distress, the number of board of directors does not have any influence to the financial distress the number of board of commissionaire does not have any influence to the financial distress, the number of audit committee does not have any influence to the financial distress, liquidity does not have any influence to the financial distress, operating capacity has positive influence to the financial distress, profitability does not have any influence to the financial distress.Keywords: Good Corporate Governance, Financial Ratio, Financial Distress